Improving the reliability of the hydromechanical gearbox model u35. 615 based on the optimization of maintenance volumes - Baiguzhina Г.Н.; Sagatbekova А.Б.; Utepova Г.А.; Izanova Л.Б. (Eurasian Journal of Applied Engineering and Technology (EJAET), 2023)
The calculation of the costs of creating operational reliability when troubleshooting the gearbox in the hydromechanical gearbox and eliminating the regularities of the restoration processes of its operation took into account the nature of the ongoing repair work. The calculation of the main deficit function is carried out in relation to the processes of restoring computer operability, including non-stationary processes in general, using a computer simulation program developed by an electronic computer (computer).